ANALISA PENGARUH AERODINAMIKA PADA MARGIN STABILITAS MORTIR LATIH 81 MM DENGAN SISTEM KOMPRESI UDARA - Akhmad Ali Imron; Agung Sugeng Widodo; Anindito Purnowidodo (Jurnal Rekayasa Mesin, 2022)
Mortar is one type of weapon used by Infantry units. One type of mortar that is widely used, especially in technical training, is the 81 mm mortar prototype produced by PT. Pindad, which has a 7.62 mm caliber munitions thruster with an average range of 110 meters. However, this mortar still has unstable aerodynamics. Therefore, this study was conducted to design a safe mortar prototype with a stability margin value, so it can determine the range and improve the troop skills. Computational fluid dynamic simulation was conducted through the ANSYS software to simulate important aerodynamic properties in this study. The angle variation of the barrel in firing used is 450,550 and 650 with compression pressure variation of 16,18, 20, 22, 24, 26, 28, 30, 32 bar. Meanwhile, the angle modification of the mortar fin is 330,440,550 and the aerodynamic simulation was carried out at 20, 30, 40 m/s speeds. The results showed that the design of an 81 mm mortar prototype which has a fin angle of 330 at a simulated speed of 20,30,40 m/s, an angle of attack of 450,550, 650 has the smallest drag force and lift force and the smallest number of postive pitch moments, but still has a standard margin of stability of about 1.57-1.81 caliber.